The String of Nodes - Leonardo Gioia (Journal Of Global Strategic Studies, 2026)
The Indo-Pacific region handles 60% of global maritime trade, and control over its territories is contested in strategic doctrine and public debate. Yet the focus on military primacy, alliances, and institutions such as ASEAN often bypasses a fundamental question: how are these exchanges materialised? Politics, economics and strategy converge in an under-theorized element: logistics. Without railways, ports, pipelines, and digital supply-chain platforms, there is no trade, integration, or durable influence. This article introduces logistical power as the capacity to project influence through infrastructure networks that bind economies, shape dependencies, and reconfigure geopolitical space. Moving beyond "debt trap" and the “String of Pearls” rhetoric, it analyses three nodes of Chinese infrastructure expansion in and around ASEAN: the Mekong basin, Kyaukpyu port (Myanmar), and the Chittagong ecosystem (Bangladesh). Extra-ASEAN cases Gwadar (Pakistan) and Hambantota (Sri Lanka) are examined to highlight how institutional density and collective negotiating capacity transform dependence from a liability into a manageable resource. The argument is that ASEAN countries are not passive terminals of Chinese logistical projection. Laos pursues calibrated dependence to escape isolation; Thailand pragmatically negotiates; Vietnam diversifies via bamboo diplomacy; Myanmar clings to Chinese support amid civil war. While logistical power can indeed redefine global hierarchies, the challenge for ASEAN is not to reject foreign infrastructure but to develop collective capacity to manage dependencies, turning its logistical crossroads into strategic leverage rather than passive vulnerability.